Effect Of Vitamin E The Dose Different In Feed For Gonad Maturation Kelabau Fish (Osteochilus Kelabau) - Nedi, Jefri; Alawi, Hamdan; ', Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted for five months from 20 May – 20 October 2013, releasing % of brood fish was done in the soil pond and ovulation was carried out in the Hatchery Laboratory and fish breeding, University of Riau. The purpose of this study was to evaluate the best dose of vitamin E added to fish pellets for egg quality of kelabau fish (Osteochilus kelabau). Applied doses of Vitamin E were 0, 100, 150, 200 mg/kg pellets. Parameters measured were the duration for gonadal maturation achievement, ovi somatic index, latency time, number of eggs ovulated, egg diameter at the end of experiment. The results showed that the maturation % gonad took place in 3 month in brood fish feed wisth vitamin E 200 mg/kg pellet. Which was shorter than that with out added with vitamin E. Latency time was 13.5 hours and the average number of ovulated eggs were 4. 807. The ovi somatic index was 0.82 % and the average diameter of eggs after treatments was 1,4 mm. Whereas the control treatment without giving Vitamin E mature gonads during maintenance 5 months in rainfed pond. water quality obtained during the study available temperature about 26 – 37 0C, pH 5 – 6, Dissolved Oxygen 1,42 – 2,20 ppm, water level 32 – 37 cm and ammonia 0,18 – 0,30 ppm.Key words: Vitamin E, Eggs quality, Osteochilus kelabau.